The Equipoise Between the Treatment of Glioblastoma and the Risk of Secondary Acute Myelogenous Leukemia: An Illustrative Case Report - Moises Harari-Turquie MD; Krishna Rekha Moturi MD; Darrell D. Horton MD; Ian Rabinowitz MD (SAGE Publishing, 2023)
We present a case report of a 56-year-old woman who was diagnosed with biopsy-proven left thalamic glioblastoma multiforme (GBM). She was treated with standard concurrent chemotherapy and radiation, as well as a 2-year period of adjuvant temozolomide. She relapsed 2 ½ years after starting her initial therapy and was treated with bevacizumab and lomustine, but she relapsed. She was then placed on a phase 1/2 clinical trial that included KHK2455 and mogamulizumab-kpkc individually and in combination for almost 4 years. She had a rapid demise due to the development of a neutropenic pneumonia and treatment-induced acute myeloid leukemia (AML) and elected for hospice care.